EVALUASI PENINGKATAN KAPASITAS HIPPAM DI KABUPATEN MOJOKERTO - Khoiruddin, Achmad (Journal of Research and Technology, 2015)
Target water services geared to meet the Minimum Service Standards (SPM) has been established, which amounted to 80% for urban areas and 60% in rural areas, as well as in supporting the achievement of the millennium development goals in 2015. The method used in the preparation of this was purposive sampling technique, namely the form of direct observation survey of the physical condition of the regions and survey potential HIPPAM existing conditions. Field observations are then correlated with secondary data research in the area of study ever conducted and data from relevant agencies. Performance results with conditions as shown in Table 21 above, it is then followed by a discussion of relevant agencies in Mojokerto to get three (3) HIPPAM which will be a priority. 3 HIPPAM election is not only based on the results of the analysis of the performance, but also consider the existing conditions in the field. Based on the results of the identification of these conditions then the election of 3 HIPPAM priority. Keywords: hippam, region, development